2010 IEEE Vehicle Power and Propulsion Conference 2010
DOI: 10.1109/vppc.2010.5729218
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of a regenerative direct-drive electromagnetic active suspension

Abstract: Abstract-The efficiency and power consumption of a direct-drive electromagnetic active suspension system for automotive applications are investigated. A McPherson suspension system is considered, where the strut consists of a direct-drive brushless tubular permanent-magnet actuator in parallel with a passive spring and damper. This suspension system can both deliver active forces and regenerate power due to imposed movements. A linear quadratic regulator controller is developed for the improvement of comfort a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The vehicle suspension system is the fundamental device for improving ride comfort and handling stability. [1][2][3][4] Recently, researchers found that the energy of the suspension vibration can be regenerated by means of magnetic suspension [5][6][7][8][9][10][11] and piezoelectric suspension. [12][13][14][15][16] In Segal and Lu, 17 the influence of suspension damping, tires, and road surface roughness on the vehicle running resistance was analyzed, and it was noted that, when the vehicle drove at a speed of 48 km/h, the damper dissipated approximately 200 W of energy.…”
Section: Introductionmentioning
confidence: 99%
“…The vehicle suspension system is the fundamental device for improving ride comfort and handling stability. [1][2][3][4] Recently, researchers found that the energy of the suspension vibration can be regenerated by means of magnetic suspension [5][6][7][8][9][10][11] and piezoelectric suspension. [12][13][14][15][16] In Segal and Lu, 17 the influence of suspension damping, tires, and road surface roughness on the vehicle running resistance was analyzed, and it was noted that, when the vehicle drove at a speed of 48 km/h, the damper dissipated approximately 200 W of energy.…”
Section: Introductionmentioning
confidence: 99%
“…Various successful works suggest that the active suspension can effectively improve the vehicle dynamics and resolve the contradictions between vehicle ride comfort and stability. For example, according to Gysen et al (2011), compared to the passive suspension, the active suspension could improve the ride comfort by 36%, or achieve a reduction of 54% in the dynamic tire load, which is beneficial to road holding performance and vehicle stability.…”
Section: Introductionmentioning
confidence: 99%
“…The device which transformed vibration energy into hydraulic energy has been proposed by Chen et al, and the results from simulations and experiments indicated that it could lead to an improvement of ride comfort and a reduction of fuel costs as well [13,14]. Gysen prototype system produced for on-board experiments [15][16][17]. In addition, a hydraulic electromagnetic shock absorber (HESA) has been studied by Fang et al, in which oils in the absorber cylinder were derived from a hydraulic rectifier bridge, flowed towards one direction and finally drove the hydraulic motor generator.…”
Section: Introductionmentioning
confidence: 99%